'Young People and Environmental Activism: The Transformation of Democratic Politics'. (3rd July 2022) - Sloam, James; Pickard, Sarah; Henn, Matt
ABSTRACT: This article provides an introduction to a Special Issue of The Journal of Youth Studies on young people and environmental politics. This volume was motivated by the wave of youth environmental activism from 2019 onwards, and by the need to address the gathering environmental crisis in the wake of the 2021 United Nations Climate Change Conference. The introduction sets the scene for the Special Issue by explaining how and why environmental activism has grown so rapidly since 2019. It introduces readers to the articles in the volume, which: study the values and attitudes that foster learning about and engagement with environmental politics amongst younger generations; examine how these values and attitudes act as mobilising forces in young people's political participation; and, investigate the role of cross-cutting issues such as education, political communication, life-style politics and also collectivism in shaping youth engagement in environmental politics. Together, these articles show how youth environmental activism is having a transformative effect upon democratic politics and democratic life in many countries across the world.